Pengaturan Tindak Pidana Pemerasan Menggunakan Foto atau Vidio Pornografi (Sekstorsi) Siber Berbasis Gender dalam Hukum Pidana Positif Indonesia - Putri, Kadziyah Atiqah; Sukmareni, Sukmareni (Universitas Pahlawan Tuanku Tambusai, 2024)
Sextortion is a cybercrime that utilizes the victim's personal content to commit extortion. The perpetrator threatens to spread the content if the victim does not comply with their request, be it a material request or a sexual act. This act is a form of online sexual violence that violates the law and can cause psychological trauma to the victim. The term sextortion was first used by the International Association of Women Judges (IAWJ), an international women's organization, in 2008. Sextortion is a combination of two words, namely sexual and exstortion. The purpose of this writing is to find out the regulation of the regulation of extortion crimes by utilizing gender-based cyber pornographic photos or videos (sexdistortion) in Indonesia's positive criminal law and also to find out whether the existing arrangements can solve the cases of sextortion that occur. This research can provide input on legal knowledge, especially those directly related to extortion that occurs on social media. This research is also expected to be a foundation for other researchers in the future. To find out more in-depth and comprehensive problems, this research uses a normative approach that involves analyzing norms, norms or values that regulate human behavior, such as in the ethical and social fields. Then the data and information obtained will be analyzed systematically so as to obtain in-depth answers about cyber gender-based extortion by utilizing pornographic photos or videos (Sextorsi) in Indonesia's positive criminal law. Based on decision Number 217/pid. B/2018/Banda Aceh District Court and decision Number 87/Pid.B/2016/Simalungun District Court can be concluded that the existing legislation in Indonesia has been able to resolve the case of sextortion.